DAMPAK COVID-19 Acutue Respitory Syindrome Coronavirus 2 (Sars-CoV-2) TERHADAP PEMBIYAAN DI BANK SYARIAH - Vicky Sanjaya.,M.,Sc; Apriya, Mery (LPPM STAI DARUSSALAM LAMPUNG, 2022)
Abstract Financing is the largest income of Islamic banks, but at the same time is the biggest source of business operation risk. Corona / Covid-19 virus related to financing in Islamic banks not only reduces the income of Islamic banks but the economic sector of a country. This study aims to analyze the impact of Covid -19 on financing in Islamic banks not only reduce the income of Islamic banks but the economic sector of a country. This study aims to analyze the impact of Covid -19 on financing in Islamic banks, not only reduce the level of income of Islamic banks, but also refers to the decline in the economic level of a country. This study aims to analyze the impact of Covid-19 on financing in Islamic banks. The method used in this research is quantitative research methods with case study design. The case study method is a learning design based on the unit level of education. This method takes the form of an explanation of a particular problem, event or situation, then students are tasked with finding alternative solutions, then this method can also be used to develop critical thinking and find new solutions from a topic being solved. The independent variable is co-19 impact. The dependent variable is Islamic bank financing. Abstrak Pembiyaan adalah pendapatan bank syariah yang terbesar, namun sekaligus merupakan sumber resiko operasi bisnis yang terbesar. Terkait virus Corona / Covid-19 terhadap pembiyaan di bank syariah bukan hanya menurunkan pendapatan bank syariah melainkan sector perekonomian suatu Negara. Penelitian ini bertujuan untuk menganalisa dampak Covid -19 terhadap pembiyaan di bank syariah, bukan hanya menurunkan tingkat pendapatan bank syariah, tetapi mengacu juga kepada turunnya tingkat perekonomian suatu Negara. Penelitian ini bertujuan untuk menganalisa dampak Covid-19 terhadap pembiayaan di bank syariah. Metode yang digunakan dalam penelitian ini adalah metode penelitian kuantitatif dengan desain studi kasus. Metode studi kasus adalah suatu desain pembelajaran berbasis tingkat satuan pendidikan metode ini berbentuk penjelasan tentang masalah, kejadian atau situasi tertentu, kemudian mahasiswa ditugasi mencari alternatif pemecahannya kemudian metode ini dapat juga digunakan untuk mengembangkan berpikir kritis dan menemukan solusi baru dari suatu topik yang dipecahkan. Variabel indepennya dampak covid-19. Variabel dependennya pembiyaan bank syariah Keywods : Covid-19, Pembiyaan, Bank Syariah